2010
DOI: 10.1016/j.vaccine.2010.09.106
|View full text |Cite
|
Sign up to set email alerts
|

Construction and immunogenicity of a recombinant fowlpox vaccine coexpressing S1 glycoprotein of infectious bronchitis virus and chicken IL-18

Abstract: Infectious bronchitis virus (IBV) poses a major threat to the chicken industry worldwide. In this study, we developed a recombinant fowlpox virus (rFPV) vaccine expressing the IBV S1 gene and chicken interleukin-18 gene (IL-18), rFPV-S1/IL18. Recombinant plasmid pSY-S1/IL18 was constructed by cloning chicken IL-18 into fowlpox virus transfer plasmid containing S1 gene and transfected into the chicken embryo fibroblasts cell pre-infected with S-FPV-017 to generate rFPV-S1/IL18. Expression of the recombinant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…IL-18 is a strong IFN-␥-inducing factor that enhances immune responses when used as an adjuvant. The concept of using IL-18 to boost immune responses after vaccination has been investigated for chicken vaccines (23,24,32,(36)(37)(38). Hung et al (21) described that the full-length and mature chicken IL-18 purified recombinant protein effectively enhanced cell-mediated and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-18 is a strong IFN-␥-inducing factor that enhances immune responses when used as an adjuvant. The concept of using IL-18 to boost immune responses after vaccination has been investigated for chicken vaccines (23,24,32,(36)(37)(38). Hung et al (21) described that the full-length and mature chicken IL-18 purified recombinant protein effectively enhanced cell-mediated and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Hung et al (21) confirmed that chicken IL-18 recombinant proteins exert in vivo biological functions through stimulating humoral and cellmediated immunities in order to enhance antigen-specific immunity and vaccine efficacy. Although many studies have shown that recombinant ChIL-18 boosts the immune responses to avian virus vaccines (22)(23)(24), few studies have investigated the modulatory effect of using a eukaryotic expression plasmid carrying ChIL-18 as a molecular genetic adjuvant to enhance these vaccines. In this study, we cloned the full-length ChIL-18 gene from specificpathogen-free (SPF) chicken embryo spleen cells and report on a eukaryotic expression plasmid carrying ChIL-18 as a genetic adjuvant, coadministered with an inactivated NDV vaccine, which induced strong immune responses in chickens at both the humoral and cellular levels.…”
mentioning
confidence: 99%
“…Delivery of the spike using attenuated strains of other pathogens, including Mycoplasma gallisepticum vaccine strain (Shil et al, 2011) and recombinant baculoviruses (Zhang et al, 2014) showed only partial protection against challenge with homologous IBV. Vector vaccines might be improved by addition of immune-related molecules, as these can reduce clinical symptoms and viral RNA levels (Chen et al, 2010;Shi et al, 2011;Wang et al, 2009;Zeshan et al, 2011). Importantly, when cloning into a DNA plasmid or viral vector, the particular sequence of the S1 domain has to be taken into account, as already one amino acid mutation can reduce the ability to confer protection against challenge considerably (Toro et al, 2014a,b).…”
Section: Viral Vectors and Dna Plasmidsmentioning
confidence: 99%
“…The report has indicated that administering ChIL-18 may be a novel approach for protecting chicken from currently circulating avian influenza and Newcastle Disease virus strains [Rahman et al, 2013]. Many studies have shown that recombinant ChIL-18 boosts the immune responses to avian virus vaccines [Degen et al, 2005;Chen et al, 2010;Rahman et al, 2013], and in vitro studies have recently shown that, similar to IL-1 [Degen et al, 2005], IL-18 overexpression inhibits hepatitis B virus replication in a hepatoma cell line [Chen et al, 2010]. IL-18 is also required for the activation of NK cells in response to infections with vaccinia virus and murine cytomegalovirus and plays a critical role in antiviral defense [Su et al, 2011].…”
mentioning
confidence: 99%